Legitimating genre: The discursive turn to quality in early 1990s science fiction television. - Howell, Charlotte E. (Critical Studies in Television, 2017)
This essay analyses how this discourse of science fiction quality was created in the early 1990s through newspaper critics’ writings about Quantum Leap, Star Trek: The Next Generation and The X-Files. Nine categories of quality – positive or negative evaluations of the science fiction programmes – arise in the discourse, often using categories independent of or in opposition to genre as quality markers. These strategies make transparent the active process of legitimation within this particular historical moment, pushing the genre construction in relation to quality beyond The Twilight Zone and Star Trek as lone exemplars.